A Study of drug utilization pattern in gynaecology out-patient department of a tertiary care hospital - Nandeshwar, Manish B.; Chakravorty, Ashish D. (International Journal of Research in Medical Sciences, 2019)
Background: Gynaecological diseases are common in India because of socioeconomic, hygienic and literacy problems. Gynaecological drugs are one of the strong selling drugs in pharmaceutical market. Drug utilization research facilitate appropriate use of drugs in patient, minimize the adverse event and lead to better patient outcome. So, the present study was carried out to examine the patterns of drug prescription. Methods: A retrospective, observational study was done by collecting the prescriptions of the patients who attended the Gynaecology out-patient department in our institute for the period of six months. Total 300 prescription were collected and analysed. Patient’s demographic data, total number and category of drugs prescribed, percentage of individual drug and their dosage forms, drugs prescribed by generic name, brand names and percentage of drugs prescribed from essential drug list were analysed. Results: The mean age of presentation was 36.6±10.98 years. Among infective group breast abscess were common and among non-infective cases dysmenorrhea was most common. Out of 754 drugs prescribed, minerals were most commonly prescribed (42.70%) followed by antimicrobials (24.53%). Tablet form were prescribed more commonly (96.02%) followed by capsules (2%) and injections (1.06%). The average no. of drugs per prescription was 2.51±1.26 SD. Percentage of drugs prescribed by generic name were 98.01% and drugs prescribed from essential drug list were 85.41%. Conclusions: The overall drug use pattern in our study correlates with various gynaecological diseases. Majority of the women from rural background depend on primary health services for gynaecological diseases in their areas so, strengthening of gynaecological health care services reduce the morbidity among the women from rural areas.